2022
DOI: 10.1002/mp.15868
|View full text |Cite
|
Sign up to set email alerts
|

Clinical acceptability of fully automated external beam radiotherapy for cervical cancer with three different beam delivery techniques

Abstract: Purpose To fully automate CT‐based cervical cancer radiotherapy by automating contouring and planning for three different treatment techniques. Methods We automated three different radiotherapy planning techniques for locally advanced cervical cancer: 2D 4‐field‐box (4‐field‐box), 3D conformal radiotherapy (3D‐CRT), and volumetric modulated arc therapy (VMAT). These auto‐planning algorithms were combined with a previously developed auto‐contouring system. To improve the quality of the 4‐field‐box and 3D‐CRT pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The RPA is a web‐based system that uses artificial intelligence to simplify the planning process. The current version of the RPA can create plans for treating cancers of the head and neck, chest wall, cervix, and whole brain, with more sites under development 19–28 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The RPA is a web‐based system that uses artificial intelligence to simplify the planning process. The current version of the RPA can create plans for treating cancers of the head and neck, chest wall, cervix, and whole brain, with more sites under development 19–28 …”
Section: Methodsmentioning
confidence: 99%
“…The current version of the RPA can create plans for treating cancers of the head and neck, chest wall, cervix, and whole brain, with more sites under development. [19][20][21][22][23][24][25][26][27][28] For the RPA to generate treatment plans, the user must input a computed tomography (CT) scan and the prescription information for each patient. That information is then verified by the users to ensure that it matches the intended final treatment plan before the RPA begins the automated planning process.…”
Section: The Rpamentioning
confidence: 99%
“…10 Previous study has also explored producing clinically acceptable VMAT plans automatically for cervical cancers based on automatically segmented contours. 11 The goal of this project was to assess whether the entire VMAT planning process, including both segmentation and plan optimization, could be automated to achieve high clinical acceptability without user interventions for rectal cancers, using a 3D CNN architecture and an automated RapidPlan program. The study examined the quality of plans generated based on autosegmentations and evaluated holistically the feasibility and clinical impacts of using an end-to-end system in producing consistent and clinically acceptable plans, all based on extensive physician evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…showed that RapidPlan can be used to achieve high‐quality automated plans consistently, even for challenging disease sites such as head‐and‐neck regions 10 . Previous study has also explored producing clinically acceptable VMAT plans automatically for cervical cancers based on automatically segmented contours 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation